Phosphate-Based Self-Immolative Linkers for Tuneable Double Cargo Release - Šimon, Petr; Tichotová, Markéta; García Gallardo, María; Procházková, Eliška; Baszczyňski, Ondřej (Chemistry (Weinheim an der Bergstrasse, Germany), 2021)
Phosphorus-based self-immolative (SI) linkers offer a wide range of applications, such as smart materials and drug-delivery systems. Phosphorus SI linkers are ideal candidates for double-cargo delivery platforms because they have a higher valency than carbon. A series of substituted phosphate linkers was designed for releasing two phenolic cargos through SI followed by chemical hydrolysis. Suitable modifications of the lactate spacer increased the cargo release rate significantly, from 1 day to 2 hours or 5 minutes, as shown for linkers containing p-fluoro phenol. In turn, double cargo linkers bearing p-methyl phenol released their cargo more slowly (4 days, 4 hours, and 15 minutes) than their p-fluoro analogues. The α-hydroxyisobutyrate linker released both cargos in 25 minutes. Our study expands the current portfolio of SI constructs by providing a double cargo delivery option, which is crucial to develop universal SI platforms.
Keywords: fosfáty; phosphate linkers; photoactivation; Drug Delivery Systems; double cargo release; 31P NMR spectroscopy; lékové transportní systémy; self-immolation; Phosphates